2011
DOI: 10.1590/s1413-86702011000500008
|View full text |Cite
|
Sign up to set email alerts
|

Spatial exploration of Streptococcus pneumoniae clonal clustering in São Paulo, Brazil

Abstract: Objectives:To examine the spatial distribution of Streptococcus pneumoniae and its clonal patterns collected between 2002 and 2006 in São Paulo, Brazil. Methods: As part of an observational study in São Paulo city, Brazil, S. pneumoniae isolates routinely cultured from blood, respiratory specimens, or cerebrospinal and other profound fluids were selected. Additionally, only isolates with either penicillin (PEN) intermediate (I) or resistant (R) status on routine antibiogram were included, in order to obtain a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…20 Data from Brazil are still scarce and fragmented. Some studies have shown low 21,22 or no 23 rates of non-susceptibility to penicillin, whereas others have indicated rates around 20%; 24-25 serotypes 14, 23F, 6B, and 19F have been most commonly associated with this resistance in brazilian studies. 24,25 Full resistance (MIC >4.0 mg/ml) to penicillin was not found among the isolates included in this study.…”
Section: Discussionmentioning
confidence: 98%
“…20 Data from Brazil are still scarce and fragmented. Some studies have shown low 21,22 or no 23 rates of non-susceptibility to penicillin, whereas others have indicated rates around 20%; 24-25 serotypes 14, 23F, 6B, and 19F have been most commonly associated with this resistance in brazilian studies. 24,25 Full resistance (MIC >4.0 mg/ml) to penicillin was not found among the isolates included in this study.…”
Section: Discussionmentioning
confidence: 98%
“…22,23 Geospatial analyses are underutilized for studying antimicrobial resistance and have not previously been applied to H. pylori. Globally, geospatial analyses have been useful for understanding the distribution of infection in antimicrobial-resistant Staphylococcus aureus, 24 Streptococcus pneumoniae, 25 and Escherichia coli. 26 Given the large variation in H. pylori resistance rates, a better understanding of the geospatial distribution of both infection and resistance, and its influence on risk factors for resistance, is needed to guide eradication therapy.…”
Section: Introductionmentioning
confidence: 99%
“…KDE helps identify the presence of clusters and irregularities [ 29 ]. This tool requires a radius to determine the circular neighborhood around each point, where that point will have influence, otherwise speaking, KDE determines how the influence of a point extends in the given radius [ 14 , 16 , 19 ]. We arbitrarily assume that each home address of a given patient could have a radius of influence of 250 m.…”
Section: Methodsmentioning
confidence: 99%